EP2 and EP4 blockade prevents tumor-induced suppressive features in human monocytic myeloid-derived suppressor cells - Cuenca-Escalona, Jorge; Subtil, Beatriz; Garcia-Perez, Alba; Cambi, Alessandra; de Vries, I. Jolanda M.; Flórez-Grau, Georgina (Frontiers in Immunology, 2024)
Tumors educate their environment to prime the occurrence of suppressive cell subsets, which enable tumor evasion and favors tumor progression. Among these, there are the myeloid-derived suppressor cells (MDSCs), their presence being associated with the poor clinical outcome of cancer patients. Tumor-derived prostaglandin E2 (PGE2) is known to mediate MDSC differentiation and the acquisition of pro-tumor features. In myeloid cells, PGE2 signaling is mediated via E-prostanoid receptor type 2 (EP2) and EP4. Although the suppressive role of PGE2 is well established in MDSCs, the role of EP2/4 on human MDSCs or whether EP2/4 modulation can prevent MDSCs suppressive features upon exposure to tumor-derived PGE2 is poorly defined.In this study, using an in vitro model of human monocytic-MDSCs (M-MDSCs) we demonstrate that EP2 and EP4 signaling contribute to the induction of a pro-tumor phenotype and function on M-MDSCs. PGE2 signaling via EP2 and EP4 boosted M-MDSC ability to suppress T and NK cell responses. Combined EP2/4 blockade on M-MDSCs during PGE2 exposure prevented the occurrence of these suppressive features. Additionally, EP2/4 blockade attenuated the suppressive phenotype of M-MDSCs in a 3D coculture with colorectal cancer patient-derived organoids. Together, these results identify the role of tumor-derived PGE2 signaling via EP2 and EP4 in this human M-MDSC model, supporting the therapeutic value of targeting PGE2-EP2/4 axis in M-MDSCs to alleviate immunosuppression and facilitate the development of anti-tumor immunity.